Different Methods of Studying Root Canal Morphology of Human Tooth: A Review (Bangladesh Journal of Dental Research & Education, 2015)
Successful root canal therapy requires an in-depth knowledge of root canal morphology.False assumptions about the root canal anatomy of teeth may lead to misdiagnosis, missed canals, improper debridement and breakage of root canal instruments during root canal treatment. The objective of this paper was to review the various methods used to study and understand root canal systems. The complexity of root canal morphology presents a challenge to any clinician. Any attempt to perform root canal therapy must be preceded with a thorough understanding of the anatomy of both the pulp chamber and the root canal system.Several methods have been used to examine the root canal system ranging from in vitro methods such as sectioning of teeth, metal castings to advanced in vivo tomographic imaging, along with the use of magnificationBangladesh Journal of Dental Research and Education Vol.5(2) 2015: 59-63